Short Paper: IoT: Challenges, projects, architectures - Gazis, Vangelis; Goertz, Manuel; Huber, Marco; Leonardi, Alessandro; Mathioudakis, Kostas; Wiesmaier, Alexander; Zeiger, Florian (2015 18th International Conference on Intelligence in Next Generation Networks, 2015)
Internet of Things (IoT) is a socio-technical phenomena with the power to disrupt our society such as the Internet before. IoT promises the (inter-) connection of myriad of things proving services to humans and machines. It is expected that by 2020 tens of billions of things will be deployed worldwide. It became evident that the traditional centralized computing and analytic approach does not provide a sustainable model this new type of data. A new kind of architecture is needed as a scalable and trusted platform underpinning the expansion of IoT. The data gathered by the things will be often noisy, unstructured and real-time requiring a decentralized structure storing and analysing the vast amount of data. In this paper, we provide an overview of the current IoT challenges, will give a summary of funded IoT projects in Europe, USA, and China. Additionally, it will provide detailed insights into three IoT architectures stemming from such projects.